2021
DOI: 10.1002/cb.1921
|View full text |Cite
|
Sign up to set email alerts
|

The impact of autobiographical memory on brand retrieval and purchase intention

Abstract: Autobiographical memory involves mentally reliving past episodes that are personally relevant. Psychology research shows that it has remarkable bearing on one's life, including the accomplishment of tasks, self‐enhancement, self‐preservation and attaining goals. Yet, the understanding of autobiographical memory in consumer behaviour research is much more limited. Accordingly, the present study evaluates the impact of two cognitive mechanisms resulting from personal past‐usage experiences linked to the product … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 76 publications
0
0
0
Order By: Relevance
“…Park and Hastak, 1994) and even purchase intentions (Stocchi et al, 2021). For example, Stocchi et al (2021) found that accessible product category knowledge reduced brand retrieval and intention to purchase brands in that category. They argued that activation that spreads across large memory networks dissipates to make it less likely that any one node reaches activation.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
See 4 more Smart Citations
“…Park and Hastak, 1994) and even purchase intentions (Stocchi et al, 2021). For example, Stocchi et al (2021) found that accessible product category knowledge reduced brand retrieval and intention to purchase brands in that category. They argued that activation that spreads across large memory networks dissipates to make it less likely that any one node reaches activation.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…I like fast cars]) memories to construct mental representations of common features and characteristics of products within that category (e.g. Cowley and Mitchell, 2003;Stocchi et al, 2021). Understanding the attribution of human-like values to product categories may enable researchers to not only examine differences between product categories, but also to examine the impact of fit with product and consumer values on consumer decisions.…”
Section: Plain Language Summarymentioning
confidence: 99%
See 3 more Smart Citations